Benefícios coletivos: Uma proposta de definiç\~ao e classificaç\~ao - Luciana Jaccoud; Marina Brito Pinheiro; Ana Cleusa Serra Mesquita; Claudia Baddini Curralero; Liliane Cristina Gonçalves Bernardes (Instituto de Pesquisa Econômica Aplicada (IPEA), 2025)
– This work aims to contribute to the debate on social security by shedding light on the issue of collective benefits. Considering that different perspectives can be mobilized around the issue, the text carries out a classification exercise of collective benefits based on three approaches: i) types of beneficiaries; ii) types of provision and delivery strategies; and iii) outcomes. The sections of the text therefore focus on defining and analysing collective benefits from these three perspectives, providing examples and proposing categories within each of these groups. After presenting each approach, the classification is revisited and presented in the form of a proposed typology. This exercise supports the possibility of thinking about different dimensions for categorising collective benefits and suggests promising possibilities for developing indicators that can make each type of collective benefit more visible.
Keywords: I31; 330; collective benefits; social indicators; health; social assistance; social security; social protection